Santa Cruz and O’Higgins: two anniversaries - Cayo, Percy (1992)
The year ending recalled, among others, two anniversaries: the hundred fiftieth anniversary of the death of Chilean hero Bernardo O'Higgins, and the bicentennial of the birth of Andres de Santa Cruz Calahumana. The author recalls the first, its contribution to the cause of freedom Chilean and Peruvian and nineteen years of his life he spent in exile among us. Of the second, his conviction always meet the former territories of Upper and Lower Peru, trying to restore the old unit that centuries of common life had given them.